The bidirectional relationship between sarcopenia and disability in China: a longitudinal study from CHARLS - Liu, Li; Zhang, Yan; Shi, Yan; Wu, Lanxin; Meng, Lixue; Zhao, Ting (Frontiers in Public Health, 2024)
Objectives: Sarcopenia and disability are important issues affecting the health of Chinese older adults. The aim of this study was to investigate the bidirectional association between sarcopenia and disability in Chinese older individuals. Results: In stage I, 65 (16.80%) new cases of possible sarcopenia, 18 (4.65%) cases of sarcopenia and 9 (2.33%) cases of severe sarcopenia were observed in the disabled older adults and 282 (10.96%) new cases of possible sarcopenia, 97 (3.77%) cases of sarcopenia, 35 (1.36%) cases of severe sarcopenia were observed in the older adults without disability. The OR (95% CI) for sarcopenia in older individuals with disability compared to individuals without disability was 1.61 (1.25-2.07). After adjusting for all covariates in 2011, the OR (95% CI) value for the disabled individuals versus individuals without disability was 1.35 (1.02-1.79). Subgroup analyses showed that disabled participants aged < 80 years had a higher risk of sarcopenia (OR = 1.42, 95% CI: 1.07-1.89). In stage II, 114 cases (33.83%) in the possible sarcopenia patients, 85 cases (28.91%) in the sarcopenia patients, 23 cases (35.94%) in the severe sarcopenia patients, and 501 cases (16.10%) in the individuals without sarcopenia showed symptoms of disability. The OR (95% CI) for disability was 2.66 (2.08-3.40) in the possible sarcopenia patients, 2.12 (1.62-2.77) in the sarcopenia patients, and 2.92 (1.74-4.91) in the severe sarcopenia patients, when compared with the non-sarcopenia patients. After adjusting for all covariates in 2011, the OR (95% CI) values were as follows: 2.21 (1.70-2.85) in the possible sarcopenia patients, 1.58 (1.14-2.19) in the sarcopenia patients, and 1.99 (1.14-3.49) in the severe sarcopenia patients, as compared to the older adults without sarcopenia. Subgroup analyses showed that women with possible sarcopenia had a higher risk of disability than men with possible sarcopenia (OR = 2.80, 95% CI: 1.98-3.97). In addition, participants aged < 80 years with sarcopenia or severe sarcopenia had a higher risk of disability (OR=2.13, 95% CI: 1.52-2.98; OR=2.98, 95% CI: 1.60-5.54). Conclusion: The onset of disability increase the risk of incident sarcopenia, furthermore, baseline sarcopenia predicts future disability in older adults.